Gender & interculturality in university scholarship programs, Arequipa (Peru): Reflections on equality and differences - Gongora Fernández, Gleny (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The search for effective gender equality is in Peru´s public interest. A valid mechanism to build equal relations and ensure social equality; especially in access to higher education opportunities, which has been increasing due to the demand of young people to pursue a university career either by their own means or obtaining state scholarships. Faced with diverse and underprivileged groups at a local and national level, which are supposed to have the same rights, privileges, and participation. That is why this text examines criteria of gender, interculturality, and includes the opinions of scholarship recipients.